Implementation Effect and Policy Improvement of Rural Teachers'Targeted Training - LIU Jia (Jiaoshi jiaoyu xuebao)
By 2022, 28 provinces have implemented the policy of targeted training of rural teachers, covering a wide range and a large scale of training. The directional training of rural teachers is directly related to the quality of rural teachers, which affects the high-quality and balanced development of compulsory education and the revitalization of rural education. By using the qualitative and quantitative evaluation method, this study analyzes the implementation effect of the targeted training of rural teachers and finds that the current training presents a "triple-balance" and "triple-imbalance" supply-demand pattern.First, in terms of the number of trained talents, the enrollment plan of targeted normal university students is balanced with the actual demand, while the actual employment is unbalanced with the demandSecond, in terms of the discipline structure of talent training, the supply of targeted normal university students is balanced with the overall needs of the county, but unbalanced with the actual needs of rural schools. Third, in terms of the quality of personnel training, the professional quality of targeted normal university postgraduates is good and balanced, while their teaching competence in rural schools is poor and unbalanced. In order to realize the policy and adapt to the new situation of population change, it is necessary to add new "three orientations" on the basis of the original "targeted enrollment, targeted training and targeted employment" to cope with the "triple imbalance": the first is the quantitative training to meet the demand of teachers in rural education; the second is the targeted school training to meet the demand of subject structure of rural schools; the third is the qualitative training to meet the quality and ability needs of rural teachers.